(untitled) (Universal International Scientific Journal, 2026)
This article examines the manifestations of bullying in school and how it affects children’s learning. It examines how physical, psychological, social and cyberbullying can occur among students. It also examines the impact of bullying on students’ self-confidence, social skills, friendships and school performance. It also discusses the measures that schools, teachers, parents and society can take together to prevent and combat bullying.